Promotional Strategy Planning for DOCI RAMEN (The Indonesian Journal of Business Administration, 2013)
The culinary world today is growing rapidly along with the progress of time. Doci Ramen is one of the businesses that operate in middle 2012. On the other hand, the promising oppurtunity creates a whole different level of competition in this market. With so many competitors offering similar products, Doci Ramen has to come up with an execellent business plan to survive the harsh rivalry. So far, doci rame has not reached its target and still pretty unheard of the study was conducted on Doci Ramen by analysing external an internal factors in order to get the root cause of failure to achieve the revenue target. This research was look up the potential customers’ dwelling around Jl. Dipatiukur throught focus group discussion, questionnaires and interviews. The research then produced an analysis of potential customers and their consumption patterns,the result of this research are how lack of advertisement and promotions for new comers influenced the fact that not many people will know of the newly established place. Doci Ramen was also focused on the promotional activity that conducted inside the Doci Ramen and intended for consumers who ready know and have visited the Doci Ramen, while the external promotion activites that sould research to reach the potential costumers that has never visited. The result of this research will become the foundation of new business strategy solution on how to create a better brand awareness both in its business to customer by reaching the target market with intergrated marketing commnuncation as weel as in its business to business by building up a good partnership between its business partner. The key objective in this new scheme is to raise public awareness which result better revenue for Doci Ramen in the future. The new promotional strategic implementation will involve the restaurants’ management with help of teh necessary agents from external resources for duration of one year focusing in B2B and B2C plans. This short term period promotion marketing startegy wiil help Doci Ramen to get its short term goals and aids the Doci Ramen to achieve the intended investment plang in long termKey words: promotion strategy, brand awareness, culinary industry